Phosphorus flow analysis for Malawi: identifying potential sources of renewable phosphorus recovery - Mnthambala, Frank; Tilley, Elizabeth; Tyrrel, Sean F.; Sakrabani, Ruben (Elsevier, 2021)
Population growth and dietary needs changes have exerted pressure on phosphorus (P) reserves, and the future availability of P fertilisers is uncertain. Most Malawian soils have low P and farmers apply P fertilisers to harvest enough food. Scarcity of chemical P fertilisers and rising prices will affect Malawi's food security. To avert the impact of P future uncertainty a P flow analysis (PFA) was conducted to characterise and quantify sources, flows, and sinks of P to determine options for waste minimisation, recovery, and chemical fertiliser use reduction for Malawi. The PFA results highlighted that; there are 35000 Mg of recyclable organic P annually, which is over two times Malawi's annual P fertiliser demand (14000 Mg). Currently, only 16% of the organic P is recycled to agriculture. Chemical P fertiliser represents 66 % of the P fertiliser used for crop production. Manure is the most recycled organic P source (38 % recycled), followed by organic solid waste (6%), and crop residues (5%). Annually, 9000 Mg of P is transferred to faecal matter, but none is recycled. Overall, Malawian soils have a negative P balance of -4000 Mg. Malawi can reduce its dependence on imported chemical P if recycling of organic P source is adopted. However, regulations should be put in place to control the quality of organic fertilisers
Keywords: Substance flow analysis software (STAN); Material flow analysis (MFA); Malawi; Phosphorus